Effect of roughness of hypo-and hyper-eutectic Al-Si piston alloy on wear characteristics under lubrication - Riyadh A., Al-Samarai; Haftirman, Dr.; Khairel Rafezi, Ahmad, Dr.; Yarub, Al-Douri, Dr. (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis, Malaysia.